Cyclosporin A causes impairment of the ventral prostate tissue structure of Wistar rats - Freitas, K. M.; Monteiro, J. C.; Gomes, M. L. M.; Taboga, S. R. [UNESP]; Dolder, H. (Sage Publications Ltd, 2012)
Cyclosporin A (CsA) is an immunosuppressive drug widely used in medicine to reduce the immune system activity and, therefore, the risk of organ rejection after transplantation. However, many side effects can be related to its use, such as, reduction in serum testosterone levels due to damage of the testis structure and, consequently, male infertility. The present study aims to evaluate the effects of chronic CsA administration on the ventral prostate tissue ( 1 5 mg/kg per d, for 56 days). Stereological, morphometrical, morphological and ultrastructural observations were employed. The plasmatic testosterone and glucose levels were measured. An androgen receptor (AR) immunohistochemical method was applied on ventral prostate sections. Apoptosis was detected with the terminal deoxynucleotidyl transferase dUTP nick end labeling technique. CsA treatment caused reduction in plasmatic testosterone levels and an increase in glycemia. The volume of all ventral prostate tissue components (lumen, epithelium and muscular and nonmuscular stroma) and ventral prostate weight were reduced in the CsA-treated group. Light and transmission electron microscopy confirmed epithelium atrophy of treated animals. There was no alteration of AR expression or apoptotic index. CsA chronic treatment in the therapeutic doses caused damage to prostate tissue of adult Wistar rats, probably due to increase in the glucose levels and reduction in the plasmatic testosterone levels.
Keywords: Immunosuppressive drug; Male reproduction; prostate toxicity